Taxonomic update and four new distribution records of Allium heterophyllum (Amaryllidaceae) in China - Cheng, Rui-Yu; He, Xing-Jin; Xie, Deng-Feng (Phytotaxa, 2026)
Allium heterophyllum (sect. Rhizirideum) was initially described based on a single population and preliminarily assessed as Near Threatened (NT). Here, we present a comprehensive update on its taxonomy and conservation status based on extensive field investigations of five wild populations, combined with morphological and molecular analyses. We discovered key diagnostic characteristics previously unrecorded, notably vegetative propagation via rhizome bulblets, dynamic scape curvature during anthesis, and leaf heteroblasty between juvenile and adult plants. Significant intraspecific variation was also documented in leaf cross-section morphology, floral coloration (white vs. pale purple), and the presence or absence of nectaries. To clarify its phylogenetic position, we conducted a reconstruction using 166 ITS sequences and 113 complete chloroplast genomes, encompassing all 26 recognized species within the section. Allium heterophyllum was resolved as a distinct monophyletic clade within sect. Rhizirideum, although cytonuclear discordance was observed: the nuclear topology placed it sister to the A. burjaticum complex, while the plastid topology resolved it as sister to the A. senescens clade. Based on its expanded distribution in Henan and Shaanxi provinces and a stable population size of approximately 10,000 individuals, we recommend revising its conservation status to Least Concern (LC). Finally, a revised morphological description and an updated identification key for all 26 recognized species of sect. Rhizirideum are provided.